Recreation of the 1977 electoral campaign in the film El disputado voto del Señor Cayo: Investigation and comparison with Miguel Delibes’s eponymous novel - Úrbez Fernández, Pablo (Hispania Nova, 2021)
The spanish film El disputado voto del señor Cayo was produced in 1986, and it is based in a book from Miguel Delibes published in 1978. In the film, which was directed by Antonio Gimenez Rico, there are a correct vision of the social-politic surround of this epoch, the development of the electoral campaign of the first democratic elections and the anticipation way they made the political programs to bring the democracy. In addition, the film exposes the contrasts between the urban and rural worlds, literate and illiterate society, and the generational change of the Transition are exposed. This paper has as more principal objective to expose the value of the film as a way to understand the electoral campaign of 1977, and in a second place to analyse the plot, showing its differences with the Delibes’s book and studying its cinematographic features.